Improving Teaching Quality through Industry Experience and Communication in Maritime Vocational Education - Kwartama, Agung (Journal for Teaching and Education for Scholars, 2025)
This study aims to examine the influence of industry experience and communication on enhancing teaching quality in maritime vocational education at the National Maritime Academy in Jakarta Raya. In today’s increasingly competitive global landscape, the quality of vocational education is critical—particularly in the maritime sector, which demands both hands-on practical skills and comprehensive theoretical knowledge. Employing a quantitative research design, data were collected through questionnaires administered to lecturers and students at the academy. The data were analyzed using descriptive and inferential statistical methods to explore the relationship between industry experience, effective communication, and teaching quality. The findings indicate a significant positive correlation between lecturers’ industry experience and teaching effectiveness. Additionally, effective communication was found to foster improved lecturer–student interaction, contributing to a more conducive and engaging learning environment. The study concludes that incorporating industry experience into academic practice and enhancing communication skills are strategic steps to improve the quality of maritime vocational education.